Physical and mechanical state of cantilever triangular plates - Akhmediyev, S.K.; Khabidolda, O.; Vatin, N.I.; Yessenbayeva, G.A.; Muratkhan, R. (JMMCS, 2023)
In this paper, the bending of cantilever triangular plates at the same angles of inclination of the side edges to the base is investigated. Due to the complexity of the boundary conditions, a numerical finite difference method is applied using a grid of scalene triangles that fits well into the contour of the plate. To solve the problem of an acute angle at the top of the plate, the method of combining the results of calculating a cantilever bar of variable bending stiffness with similar results of calculating a triangular plate supported along the contour using a reduction factor is applied. The results of deflections of the cantilever triangular plate at different angles of inclination of the side edges to the base are given. The theoretical provisions and applied results of this study can be used both in scientific research and in engineering design.
Keywords: triangular plate; numerical method; grid method; deflection; bending stiffness; rod analogy; reduction factor